Pengaruh Dukungan Sosial Teman Sebaya Terhadap Penyesuaian Diri Siswa SMP - Saputri, Disa Magfira; Silalahi, Micha Felayati; Fitriani, Dian; Riyadi, Nur Eka Wahyuningsih (LPPM Institut Pendidikan Nusantara Global, 2024)
This research examines how peer social support affects the self-adjustment of SMP students in the Mantikulore Sub-District. This research employed a survey with a quantitative approach. There are 138 students among the research subjects. The research instrument used to collect data was a questionnaire. According to the descriptive results, 67 students (48%) have good peer social support. The descriptive analysis of self-adjustment results indicated that 87 students (63%) have high self-adjustment. The data was statistically processed, and hypothesis testing used traditional assumption tests and sophisticated analytical tests. Based on the t-test results, the descriptive analysis indicates the influence of peer social support, with a t-count of 6.856 and a t-table of 1.977 at a significance level of 5%. The research findings suggest that the coefficient of determination (R2) is 0.507, indicating that peer social support influences students' self-adjustment by 50.7%, whereas other variables affect 49.3%.